Penggunaan Model CIPP dalam Evaluasi Program Matrikulasi di Pascasarjana IAIN Pekalongan - Ahmad Taufiq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to evaluate the Arabic language matriculation program at the Postgraduate IAIN Pekalongan, using an analysis of context, input, process and product evaluation models. This research uses quantitative research methods with. The results of the evaluation 1) context aspects, namely the understanding of the Arabic language matriculation program is very high or very good, it can be seen that there is a match between program content, curriculum structure, and program objectives with the understanding of lecturers and students showing a positive relationship. 2) at the input aspect level, it is in the very good category, academic qualifications and competency qualifications in the Arabic language matriculation field for educators show a good category, but there is one indicator that still needs to be improved, namely the supporting infrastructure for the Arabic language matriculation program has not been maximized; 3) evaluation of the process aspect is in the sufficient category, in the implementation of learning, learning strategies and methods as well as the use of learning tools or media have not been maximized, then the time allocation has not gone according to plan or has not been effective; 4) evaluation of product aspects. are in the sufficient category. The achievements set in the Arabic language matriculation program have not fully met the target.